PENGUJIAN KOMPOSISI BAHAN DASAR DAN DOSIS TRICHOKOMPOS TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq) - Anggraini, Dewi; Tabrani, Gunawan; Ariani, Erlida (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
The aim of the study was to obtain the better growth oil palm seedlings by providing trichocompos from basic ingredients and different doses. This study uses a cluster randomized design method (CRD) in 9 treatments and 3 replications.Observed including: seedling height, number of leaves, stem diameter, root canopy ratio, seedling dry weight and seedling quality index. The results showed that only the height of the oil palm seedlings was better given by the composision corn waste, market waste and cattle rumen trichocompos in 10-20 ton.ha-1 doses. Height of oil palm seedlings was increased by giving trichokompos based on corn waste or cattle rumen at doses of 15 and 20 ton.ha-1. Increased root canopy ratio increased by trichokompos based on corn waste and cattle rumen as much as 50 g.polybag-1.Keywords: Palm oil seedling, composision of basic materil and doses trichokompos